Association between pesticide exposure and the nutritional status of farmers in Sitio Rero-an, Cabatuan, Iloilo an analytical cross-sectional study - Espedido, Robyn Emielle Sibayan
Pesticides have generally been regarded as toxic chemicals that are widely used in agriculture. Populations that are highly exposed to it include production workers, sprayers, formulators, mixers, loaders and agricultural farmers. Exposure may present adverse health effects in humans, both acute and chronic, an example of which is inadequate nutritional status. Assessment of one?s nutritional status is an important component of health care for adequate nutrition is required to properly function in life. This study aimed to examine the association of pesticide exposure and body mass index (BMI) of farmers in Sitio Rero-an, Cabatuan, Iloilo. Pesticide exposure was estimated using an algorithm from the Agricultural Health Study, and anthropometric measurements were used to calculate BMI. Associations of nutrient intake and sociodemographic factors, specifically age and income, with BMI were also investigated. Nutrient intake was measured using 24.hour food recalls and FCT computations, while primary data was obtained for sociodemographics. A total of 48 farmers were subjects in the study. Descriptive statistics and bivariate correlation was used to analyze the data. Results show that the association between pesticide exposure and BMI was weakly correlated and not statistically significant (r=-0.020; p-value = 0.893). moreover, both income and the nutrient intake of farmers showed weak correlation and is not statistically significant. Only age was observed to have a significant association, albeit weak correlation, with BMI (r=-0.316; p-value = 0.029). it was therefore concluded that no association exists between pesticide exposure and BMI. It is recommended that similar studies in the future use relatively larger sample sizes, longer study time frames, and clinical test to assess both pesticide exposure and nutritional status for an overall better accuracy.